Implementation of STIFIn Concept in Tahfizh al-Qur’an Learning at SMP IT Madani Payakumbuh - Difa Dian Fadilah; Muhammad Rizqi; Efizal A (Al Bahri: Journal of Islamic Education, 2024)
In this modern era, memorizing the Qur’an has become a characteristic of various educational institutions. If we look closely at the time of the Prophet Muhammad SAW, memorizing was not a matter of speed of time but the importance of religious teachings to be understood, taught and applied in everyday life. For this reason, this article will discuss about Implementation of STIFIn Concept in Tahfizh al-Qur’an Learning at SMP IT Madani Payakumbuh. The method used in this research is qualitative method with a descriptive approach, with 48 respondents, namely class IX students of SMP IT Madani Payakumbuh. After carrying out in-depth research the author found that implemetion of STIFIn Concept in Tahfizh al-Qur’an Learning at SMP IT Madani Payakumbuh are i) Implemetion of STIFIn concept has been running for the past three years, ii) There are differences in students' memorization abilities based on the types in STIFIn concept, iii) Of the five intelligence machines that students have in memorizing the Qur’an, the Thingking type is the most efficient type in the memorization process, because the way this type works is used to being effective and produces high certainty, so this type will manage with full stability. In the future, the author hopes that this research will have a positive impact, especially at Islamic School and Teacher of Tahfizh Qur’an